2018
DOI: 10.5194/se-9-139-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the geothermal gradient across two differently aged magma-rich continental rifted margins of the Atlantic Ocean: the Southwest African and the Norwegian margins

Abstract: Abstract. The aim of this study is to investigate the shallow thermal field differences for two differently aged passive continental margins by analyzing regional variations in geothermal gradient and exploring the controlling factors for these variations. Hence, we analyzed two previously published 3-D conductive and lithospheric-scale thermal models of the Southwest African and the Norwegian passive margins. These 3-D models differentiate various sedimentary, crustal, and mantle units and integrate different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…After eliminating this source of error, we interpret the two clusters' differentiation to result mainly from the sediment layer's electrical resistivity, which indicates a change in sediment type or sea bottom heat flow (Grayver, 2021). The previously described effect of "thermal blanketing" in the southern Namibe basin (Gholamrezaie et al, 2018;Maystrenko et al, 2013), is likely a factor responsible for the differentiation of the two sediment clusters. This would mean, that the increased resistivity values of cluster sed-B are linked to a decrease in temperature away from the major depositional centre of Walvis Basin.…”
Section: Transitional Crust Along Walvis Ridgementioning
confidence: 80%
See 1 more Smart Citation
“…After eliminating this source of error, we interpret the two clusters' differentiation to result mainly from the sediment layer's electrical resistivity, which indicates a change in sediment type or sea bottom heat flow (Grayver, 2021). The previously described effect of "thermal blanketing" in the southern Namibe basin (Gholamrezaie et al, 2018;Maystrenko et al, 2013), is likely a factor responsible for the differentiation of the two sediment clusters. This would mean, that the increased resistivity values of cluster sed-B are linked to a decrease in temperature away from the major depositional centre of Walvis Basin.…”
Section: Transitional Crust Along Walvis Ridgementioning
confidence: 80%
“…These sediments may have been transported along the shelf by bottom and surface currents and likely originate from cyclic erosion-deposition phases linked to the Orange, Kuiseb, and Swakop rivers (Dingle, 1992;Dingle et al, 1987;Goslin et al, 1974). Furthermore, Gholamrezaie et al (2018) and Maystrenko et al (2013) observed increased geothermal gradients in the sediment basins along the margin, which are explained with the effect of "thermal blanketing" through the thick insulating cover. Therefore, increased heat flow in these basins can also be regarded as a potential reason for the high electrical conductance values of cluster sed-A.…”
Section: 2) the Mantle Part Of The Southern Transitional Crust Is Exc...mentioning
confidence: 99%
“…Overall, temperature observations from deep well logs would be a more suitable to validate lithospheric-scale 3-D thermal models in comparison to shallow geothermal gradients and surface heat-flow (e.g. Scheck-Wenderoth et al, 2014;Sippel et al, 2017;Gholamrezaie et al, 2018). Moreover, a good fit between observed and modeled temperature is found within the deeper parts of the 2,500-m-deep onshore well (Fig.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 83%
“…These sediments may have been transported along the shelf by bottom and surface currents and likely originate from cyclic erosion-deposition phases linked to the Orange, Kuiseb, and Swakop rivers (Dingle, 1992;Dingle et al, 1987;Goslin et al, 1974;Garzanti et al, 2018). Furthermore, Gholamrezaie et al (2018) and Maystrenko et al (2013) observed increased geothermal gradients in the sediment basins along the margin, which are explained with the effect of "thermal blanketing" through the thick insulating cover. Therefore, increased heat flow in these basins can also be regarded as a potential reason for the high electrical conductance values of cluster sed-A.…”
Section: Transitional Crust South Of Walvis Ridgementioning
confidence: 99%